Sistem brek elektromagnetik boleh kawal menggunakan arus pusar - Mohamad Zairi, Baharom (2013)
This research presents a laboratory based experimental study of a controllable electromagnetic braking system utilising eddy current. The main focus was to study parameters related to the eddy current electromagnetic braking system and to apply the system on a test study application. This study explored potential benefits over conventional braking systems, including in the reduction of brake pad wear and wear debris contamination due to hazardous materials such as copper. The objective was to design and fabricate a test rig in order to investigate the relationship between variable parameters that affect the electromagnetic braking system response and to implement the controllable system on an undertaken test case. Two test rigs were constructed for the study on the interactions of variable parameters and on the test case application. Laboratory experiments were carried out to examine the correlation between parameters such as the coil current, air gap widths, types of disc brakes, disc thickness, and number of turns of the electromagnetic coil. Two different materials, Al6061 and Al7075 were also compared in this response experiment. In the validation part of the experiment, related optimum parameters found from the response part were used in implementing the eddy current electromagnetic braking system on a stationary exercise bicycle. From the experimental results, it was found that the parameters have some effect on certain braking behaviour. Braking force increased as the coil current increased, as also with the use of a smaller air gap, larger number of coil turns and thicker disc. Three types of disc material were tested: aluminium, zinc and copper; subsequently, aluminium was found to be the best among the three. It was also found that Al6061 performed better than Al7075. The eddy current electromagnetic brake was tested for exercise purposes, taking the coil current as the controllable parameter. Increasing the coil current caused the cycling resistance to increase, and hence the intensity of the exercise also increased. From this research, it was shown that the eddy current electromagnetic brake could be successfully implemented as a controllable braking system on a test static exercise bicycle. Thus, this system has great potential to be explored as an alternative to present-day conventional braking systems